Meningkatkan Penalaran Kritis Siswa Melalui Metode PBL Pada Pak Materi Aku Citra Allah Kelas VII SMPN 5 Kelam Permai - Arkodius Angun (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The background to this research arises from the low level of critical reasoning of students at SMPN 5 Kelam Permai. Overcoming this problem requires a learning approach that can stimulate students' critical reasoning during the learning process. Problem-Based Learning (PBL) has proven to be effective in developing students' critical thinking skills through problem solving. The aim of this research is to improve students' critical reasoning and achieve learning targets in class VII SMPN 5 Kelam Permai through PBL. This research uses quantitative methods. The results of observations in cycle 1 showed that students' critical reasoning level was 69%, with learning achievement targets including 4 proficient students, 5 proficient students, and 1 adequate student. In cycle 2, there was a significant increase with the average critical reasoning of students reaching 80.5%. Learning achievement targets include 6 proficient students, 3 proficient students, and 1 decent student. The implications of these findings indicate that PBL is effective in increasing students' critical reasoning and learning ACHIEVEMENT targets. Implementing PBL can be a useful strategy for improving critical reasoning and student learning achievement targets.